An Overview of Clinical Studies on Fiber Post Systems - Idil Dikbas; Jale Tanalp (The Scientific World Journal)
Intraradicular posts are useful adjuncts in the restoration of endodontically treated teeth. These systems have undergone a significant evolution in recent years, and fiber-reinforced systems have started to be incorporated into routine clinical care more frequently. Despite the high number of laboratory studies pertaining to the characteristics of fiber posts, clinical studies evaluating their general success rates are rather limited. Since clinical investigations are reliable means to achieve information about the general behavior pattern of materials or techniques, assessment of this data will be beneficial to have a better understanding of fiber-reinforced intraradicular post systems. The purpose of this paper was to make a summary of clinical studies regarding various fiber posts. A PubMed search was conducted and articles dating back to 1990 were retrieved. The paper provides an overview of clinical studies on fiber posts specifically in the last decade as well as commentary analysis.